THE IMPORTANCE AND ROLE OF APPLICATION OF DIGITAL MARKETING STRATEGIES IN THE EDUCATIONAL SYSTEM - Erkinova Nilufar Toxir qizi (Journals Park Publishing, 2023)
Time fast in development foundation being coming system this digital is an activity . This in the article digital activity marketing system with directly depends without apply through country development basis considered education system high in paces progressive to reach effect doer factors and education in the field interstate competitiveness level in raising adding contribution analysis , society development and economic and social stability in providing reflection which role to the discussion is placed and to them solution as from high school from beginning to middle special and higher education in systems done increase possible has been digital marketing strategies application will be done .
Keywords: digital marketing, digital technology , marketing strategies , education system , higher education.